2018
DOI: 10.1556/0806.46.2018.040
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Iranian wild barley (Hordeum vulgare ssp. spontaneum) in breeding for drought tolerance

Abstract: The vast genetic resources of wild barley (Hordeum vulgare ssp. spontaneum, hereafter WB) may hold unique assets for improving barley (H. vulgare ssp. vulgare) cultivars for drought stress. To evaluate genetic potential and characterization of variation among a diverse collection of barley and WB genotypes, mostly originated from Iran, a field experiment was performed under three moisture environments (control, mild and intense drought stress) during two years (2012-2014). Considerable variation was observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Many studies have reported the richness of H. spontaneum accessions with respect to genes for resistance to major diseases (Abbott, Brown, & Burdon, 1991; Brian, Steffenson, & Bockelman, 1995; Fetch, Steffenson, & Nevo, 2003; Oğuz, Karakaya, & İsmail, 2018; Sato & Takeda, 1997; Tombuloglu et al., 2015), tolerance to major drought and salinity stresses (Barati et al., 2018; Chen et al., 2009; Ebrahim, Arzani, Rahimmalek, Sun, & Peng, 2019; Nevo & Chen, 2010; Wang et al., 2018; Yan, Chen, Cheng, Nevo, & Gutterman, 2008) and end‐use quality traits (Cai et al., 2013; Yan et al., 2008). This diversity is extensively used in breeding programs (Nevo et al., 1992) and it is estimated that 40% of the alleles are common between H. spontaneum and cultivated barley (Ellis et al., 2000; Tombuloglu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the richness of H. spontaneum accessions with respect to genes for resistance to major diseases (Abbott, Brown, & Burdon, 1991; Brian, Steffenson, & Bockelman, 1995; Fetch, Steffenson, & Nevo, 2003; Oğuz, Karakaya, & İsmail, 2018; Sato & Takeda, 1997; Tombuloglu et al., 2015), tolerance to major drought and salinity stresses (Barati et al., 2018; Chen et al., 2009; Ebrahim, Arzani, Rahimmalek, Sun, & Peng, 2019; Nevo & Chen, 2010; Wang et al., 2018; Yan, Chen, Cheng, Nevo, & Gutterman, 2008) and end‐use quality traits (Cai et al., 2013; Yan et al., 2008). This diversity is extensively used in breeding programs (Nevo et al., 1992) and it is estimated that 40% of the alleles are common between H. spontaneum and cultivated barley (Ellis et al., 2000; Tombuloglu et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to characterize the general diversity of the Hordeum CWR set, which, according to recent studies, could serve as a source of valuable genes needed in current barley breeding [ 10 , 34 , 35 ]. Special attention was paid to the resistance to biotic stresses, namely resistance to fungal diseases, which is in continuous demand, globally, for all crops [ 36 ], since pathogens spreading at a continental scale can have a strong impact on plant health.…”
Section: Discussionmentioning
confidence: 99%
“…Wild barley has been shown to be a donor of new alleles, conferring resistance to abiotic stresses such as salinity and drought, and biotic stresses such as powdery mildew, which are unique assets for barley improvement, especially in a changing climate [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%